CSN3 gene distribution frequency in camels of Almaty region (Experimental biology, 2020)
Camel breeding is the important industry of agriculture which provides the food and light industry with milk, wool, leather, etc. products. Especially, shubat obtained from camel milk due to its special taste and medical properties is in great demand in the market. In this way, in order to improve the breeding of camels in the dairy direction, it is very important to carry out selection work in this direction. The total amount of caseins that make up camel milk is about 75% of milk protein. These caseins consist of four fractions encoded by the genes CSN1S1, CSN1S2, CSN2 and CSN3: alpha s1, alpha s2, beta and κ-casein. Genetic polymorphism of the above-mentioned genes determines the quantitative and technological properties of milk. Propagation of homozygous animals by these genes is carried out in order to improve the qualitative properties of milk, namely fat content and nutrition. The most beneficial and affordable method for studying these genes is the PCR-RFLP method.In this work, there was studied the polymorphism of the CSN3 gene, which is involved in the formation of qualitative traits of milk in several two-humped camel (Camelus bactrianus) populations that are bred in farms of the Almaty region. Among the 53 camels selected for study, the «useful» cytosine frequency is 0.39. As well, among the studied populations, Hardy-Weinberg equlibrium was determined by the distribution of genotypes (χ2 = 12.1).Key words: camels, dairy productivity, kappa casein, PCR-RFLP analysis.